STUDI PERSEBARAN DEPOT AIR MINUM ISI ULANG DAN KUALITAS AIR MINUM ISI ULANG SECARA MIKROBIOLOGIS DI KECAMATAN JEBRES KOTA SURAKARTA TAHUN 2014 ( IMPLEMENTASI SEBAGAI PENUNJANG MATERI PEMBELAJARAN GEOGRAFI SEKOLAH MENENGAH ATAS KELAS X SEMESTER I PADA S - Rosyid, Adiatma (Pendidikan Geografi, 2014)
ABSTRACTThis study aims to: (1) knowing distribution of refill water depot at Jebres District, Surakarta Region, (2) knowing refill water quality microbiologicaly at Jebres District, Surakarta Region, (3) knowing factors which effect distribution of refill water depot at Jebres District, Surakarta Region. This research uses descriptive study with a spatial approach. Primary data obtained through field surveys, and secondary data obtained through documentation. The sampling technique used was saturation sampling technique that sample is according in its object totality which represents all characteristic oof data. Test the validity of the data using triangulation techniques.Based on the results of the research can be summed up into three (1) 4 from 37 depot had contaminated E.Coli and Total coliform, such as : refill water depot Sumber Agung at Mojosongo Village, refill water depot Gunung Mas at Jebres Village, refill water depot Anugerah Tirta at Jebres Village, and refill water depot Langgeng at Jagalan.(2)Distribution of refill water in Jebres District, Surakarta Region has 37 refill water depot, Mojosongo Village has large number of distribution with 17 amount of refill depot, then Jebres Village with 13 amount of refill water depot. Jagalan Village has 2 refill water depot, Purwodiningratan and Sudiroprajan, Sewu and Pucang Sawit only has 1 refill water depot. (3) Refill water distribution in Jebres District, Surakarta Region in 2014 has b een effected by spatial structure such as: Mojosongo, Jebres, Pucang Sawit, Jagalan,Sewu, Gandekan, Purwodiningratan dan Sudiroprajan. The others village have been effected by amount of its potential consumer (4)learning implementation of geography matter at Senior High School in subject of geography approachment. Keywords: Microbiologicaly Water Quality,Distribution,Refill Water Depot, Distribution Factors